Analisis Pilihan Konsumen terhadap Keputusan Pembelian Daging Ayam Broiler di Kota Kefamenanu - Sikone, Hilarius Yosef; Nugraha, Elisabeth Yulia; Bouk, Gomera; Sinabang, Maria (Fakultas Pertanian, Universitas Timor, 2024)
Consumer preference is a choice of the level of importance or level of consumer preference for a product that wants to be purchased or consumed. This study aims to analyze the attributes of broiler chicken meat products that are consumer preferences in the city of Kefamenanu, North Central Timor district, in buying broiler chicken meat. The study was conducted from February 2023 to April 2023. Janis this research is quantitative descriptive research with survey research method. Using 60 respondents, who were selected by accidental sampling method, samples were taken based on their willingness to fill out questionnaires and interviewed during a visit to broiler chicken meat traders in the new market of Kefamenanu city. The collected data will be analyzed using the Conjoint analysis tool. The results showed that the combination of attributes that are most widely preferred or become consumer preferences is broiler chicken meat with attributes: chewy textured meat, clean from feather dirt and fat, with large meat cut sizes, prices ranging from Rp 60,000-Rp 75,000, and bright meat color (yellowish white).